Combined Effect of Bypass Fat and Hormonal Protocol on the Performance of Reproductive Disorder Crossbred Cattle: - Sethy, K.; Tripathy, S.; Swain, R.K.; Mishra, S.K.; Panda, N.; Behera, K.; Panda, S.K.; Sabat, G.P.; Mishra, U. (Indian Journal of Animal Nutrition, 2022)
Bypass fat is the calcium salt of fatty acid used as a major source of energy for production and reproduction in high yielding cattle. Hormonal protocols may not be effective for treating reproductive problems in energy deficient animals. Henceforth, the current study was undertaken to evaluate the effect of hormonal protocol in reproductive disorder crossbred Jersey cattle supplemented with bypass fat. A 60 days study was conducted taking eighty reproductive disordered Jersey cattle consisting of 48 cows and 32 heifers divided into four groups having 20 animals each (containing both anoestrus (12) and repeat breeder (8).  Group T0 was control (normal feeding practices of farmer consisting of straw-based diet and locally available concentrate like wheat bran and mung chunies), T1 group: T0+ Bypass fat @ 100g/day/animal), T2 group: T1+ hormone (Double synch) and T3 group: T1+ hormone (Estra-double synch). The growth rate, blood haematological, serum biochemicals and reproductive status of the animals were assessed. Significant improvement in average daily gain and reproductive performances was observed in treated animals as compared to control. Maximum conception was achieved in group T3 (70%) followed by group T2 (60 %) and T1 (40 %). So, it was found that bypass fat along with estra double synch protocol is most suitable in field condition for preventing reproductive disorder in cross bred cattle.